Respostas
respondido por:
3
( m-3)*2 + 4( m-5) = 0
2m - 6 + 4m - 20 = 0
6m - 26 = 0
6m = 26
m = 26/6 = 13/3 ****
2m - 6 + 4m - 20 = 0
6m - 26 = 0
6m = 26
m = 26/6 = 13/3 ****
respondido por:
0
Olá,
(m-3)·x+4·(m-5) = 0
Para x=2 temos m = ?
(m-3)·2+4·(m-5) = 0
2(m)+2(-3)+4(m)+4(-5) = 0
2m-6+4m-20 = 0
2m+4m-20-6 = 0
6m-26 = 0
6m = 26
m = 26/6 = (26/2)/(6/2)
m = 13/3
(m-3)·x+4·(m-5) = 0
Para x=2 temos m = ?
(m-3)·2+4·(m-5) = 0
2(m)+2(-3)+4(m)+4(-5) = 0
2m-6+4m-20 = 0
2m+4m-20-6 = 0
6m-26 = 0
6m = 26
m = 26/6 = (26/2)/(6/2)
m = 13/3
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás